Estimativa dos valores pressóricos arteriais sistêmicos na presença dos fatores de risco cardiovascular em idosos - Peres, Cristina Ila de Oliveira (2018)
Introduction: Traditional cardiovascular risk factors (CVRs) induce thickening and arterial stiffness, raising blood pressure levels. Variables such as pulse wave velocity (PWV) and aortic index (Aix) are markers of arterial wall thickening and may contribute to the estimation of blood pressure values. Objective: To verify the influence of traditional cardiovascular risk factors, PWV and Aix in estimating blood pressure values in the elderly. Method: Cross-sectional population study with 1192 elderly people, aged 60 years or older. For the measurement of peripheral arterial pressures, an oscillometric device was used, and to measure the central pressures, the aplanation tonometry. Thus, PWV was obtained in the carotid-femoral stretch (c-fPWV), as well as Aix. For statistical treatment of the data, the software STATA, in version 15.0 was used. Simple frequency descriptive analyzes were performed for categorical variables, measures of central tendency (mean and median) and variability (standard deviation) for continuous variables. In order to verify the magnitude of the influence of the cardiovascular risk factors listed in the different pressure components, the Pearson correlation tests were applied. Next, the multivariate analysis (Stepwise) was performed for all variables that participated in the bivariate analysis, with central and brachial pressures as dependent variables. The pressure estimation formulas were derived from multivariate analyzes with inclusion of vascular wall thickening markers. The level of significance was set at 0.05. Results: The mean age of the group was 69.0  7.0 years. The systolic, diastolic and pulse pressures were: 138.7  20; 78.2  10.7; 60.4  15.3 mmHg, respectively. Central systolic, diastolic and pulse pressures were: 132.2 ± 19.3; 84.1  12.6 and 48.1  14.5 mmHg, respectively. The mean c-fPWV was 8.3 m / s, while the mean Aix was 33.6%. All pressures showed significant correlations with c-fPWV. In the multivariate analysis, it was verified that the risk factors evaluated seem to have a greater influence on the central pressures to determine their values. Conclusion: The CVR factors influenced, differently, the systemic pressure values of the elderly. The pulse wave velocity and the rate of increase participated in the composition of each pressure component.